T2 MRI visible perivascular spaces in Parkinson’s disease: clinical significance and association with polysomnography measured sleep - Meinhold, Lena; Gennari, Antonio G; Baumann-Vogel, Heide; Werth, Esther; Schreiner, Simon J; Ineichen, Christian; Baumann, Christian R; O’Gorman Tuura, Ruth (Sleep (New York, N.Y.), 2025)
Poor sleep quality might contribute to the risk and progression of neurodegenerative disorders via deficient cerebral waste clearance functions during sleep. In this retrospective cross-sectional study, we explore the link between enlarged perivascular spaces (PVS), a putative marker of sleep-dependent glymphatic clearance, with sleep quality and motor symptoms in patients with Parkinson’s disease (PD). T2-weighted magnetic resonance imaging (MRI) images of 20 patients and 17 healthy control participants were estimated visually for PVS in the basal ganglia (BG) and centrum semiovale (CSO). The patient group additionally underwent a single-night polysomnography. Readouts included polysomnographic sleep features and slow-wave activity (SWA), a quantitative EEG marker of sleep depth. Associations between PVS counts, PD symptoms (MDS-UPDRS scores), and sleep parameters were evaluated using correlation and regression analyses. Intra- and inter-rater reproducibility was assessed with weighted Cohen`s kappa coefficient. BG and CSO PVS counts in both patients and controls did not differ significantly between groups. In patients, PVS in both brain regions was negatively associated with SWA (1–2 Hz; BG: r(15) = −.58, padj = .015 and CSO: r(15) = −.6, padj = .015). Basal ganglia PVS counts were positively associated with motor symptoms of daily living (IRR = 1.05, CI [1.01, 1.09], p = .007, padj = .026) and antidepressant use (IRR = 1.37, CI [1.05, 1.80], p = .021, padj = .043) after controlling for age. Centrum Semiovale PVS counts in patients were positively associated with a diagnosis of REM sleep behavior disorder (IRR = 1.39, CI [1.06, 1.84], p = .018, padj = .11). These results add to evidence that sleep deterioration may play a role in impairing glymphatic clearance via altered perivascular function, potentially contributing to disease severity in PD patients.